Recent advances in the manipulation of circularly polarised light with cellulose nanocrystal films - Fernandes, S. N. (2022)
This work is funded by FEDER funds through the COMPETE 2020 Program, National Funds through FCT - Portuguese Foundation for Science and Technology and POR Lisboa2020 , under the projects with references POCI- 01-0145-FEDER-007688 (Reference UID/CTM/50025), UID/BIA/00329/2013, PTDC/CTM-BIO/6178/2014, M-ERA-NET2/0007/2016 (CellColor) and PTDC/CTM-REF/30529/2017. S.N. Fernandes and L.F. Lopes acknowledge the Minister of Science, Technology and Higher Education for National Funds , European Social Funds and FCT for fellowships number SFRH/BDP/78430/2011 and SFRH/BPD/84478/2012 , respectively. This work was supported by the Histology and Comparative Pathology laboratory [Electron Microscopy service] of the Instituto de Medicina Molecular João Lobo Antunes, specifically Andreia Pinto for her kind support. We would like to thank Carlos Silva for providing the C. chrysina specimen. The C. aurata specimen observed was provided by the Insect Collection of the National Museum of Natural History and Science, University of Lisbo